HEAVY METAL UPTAKE OF LEAFY VEGETABLE AND ITS HUMAN HEALTH IMPLICATION IN VEGETABLE-GROWING AREAS OF OGUN AND OYO STATE, NIGERIA - Eruola, A.O.; Ojiodu, C.C.; Eruola, G. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study assessed the heavy metal pollution extent of irrigation water and soils used for the cultivation of Jute mallow and African spinach in selected vegetable-growing areas of Ogun and Oyo states, Nigeria. Composite water, soil, and vegetable samples were collected from 11 farms in replicates. The concentrations of selected heavy metals (Copper (Cu), Chromium (Cr), Nickel (Ni), Lead (Pb), and Cadmium (Cd)) were analyzed. The geo-accumulation index (Igeo), bio-accumulation factor (BAF), hazard quotient (HQ), hazard index (HI), and cancer risk (CR) were used to assess health risk.The result revealed that while Cu, Cr, Pb, and Cd were predominant in soil, water, and in both vegetables in the majority of the farms, Ni was only found in the vegetables with higher concentration in African Spinach than the Jute Mallow. The African spinach also adsorbed Cd more than the Jute mallow in the farms. Indications revealed that Cu in vegetables may be absorbed from both the irrigation water and the soil polluted by organic manure, agrochemicals, and cattle grazing activities around the farms. While Pb and Cd pollution may be a result of vehicular emissions along the farm path and indiscriminate burning of waste on the farms, respectively. The Cr and Pb were the major contributors to both the non-carcinogenic and carcinogenic health risk in the irrigation water and soils among all the heavy metals examined, hence, the associated indirect effect on the populations using the irrigation water and soils for cultivation of vegetable. It was noted that the soils in the area were in the moderately polluted category with respect to Igeo assessment. The capacity of Jute mallow and African spinach to accumulate heavy metals in the farm locations decreased in the order of Coker > Ilaro > FUNAAB > Atan > Ado-odo > Odogbolu in Ogun state, and Kisi > Iresa > Ijaye > Lalupon > Ido in Oyo state. The regulatory authorities should be advised to provide effective controls to reduce heavy metal pollution of surface water and soils in the study areas.